2003
DOI: 10.1210/jc.2002-021302
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism Is Associated with Suppressed Circulating Ghrelin Levels

Abstract: Ghrelin stimulates GH secretion as well as appetite and food intake. To explore whether ghrelin is involved in the regulation of appetite and body weight in hyperthyroidism, circulating ghrelin levels were measured in nine hyperthyroid patients before and after medical treatment and compared with those in eight healthy control subjects. All participants were studied in the postabsorptive state and during a 3-h euglycemic hyperinsulinemic clamp. Before treatment the patients had 3- to 5-fold elevations of T(3),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
0
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 38 publications
7
58
0
4
Order By: Relevance
“…However, if this were the case, the opposite would be expected in hypothyroidism where ghrelin levels were similar to healthy controls before and after treatment. Furthermore, glucose and insulin concentrations and insulin sensitivity were normal in hypothyroidism, as previously described (23). This observation could contribute to explain why ghrelin levels were not altered in hypothyroidism.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, if this were the case, the opposite would be expected in hypothyroidism where ghrelin levels were similar to healthy controls before and after treatment. Furthermore, glucose and insulin concentrations and insulin sensitivity were normal in hypothyroidism, as previously described (23). This observation could contribute to explain why ghrelin levels were not altered in hypothyroidism.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, ghrelin levels increased in hyperthyroidism after treatment, in spite of an increase in BMI, waist-to-hip ratio and percentage of body fat and, in hypothyroidism, BMI decreased without modification of ghrelin levels suggesting an absence of relationship between ghrelin and these anthropometric changes in thyroid dysfunction. Additionally, we did not find any correlation between ghrelin and thyroid hormone levels as previously described (23).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…It appears that the hyperphagia of hyperthyroidism is not mediated by circulating ghrelin (Katergari et al, 2008). Circulating plasma ghrelin levels are reduced in hyperthyroidism as compared to the euthyroid state (Altinova et al, 2006a), exhibit a positive correlation with thyroid stimulating hormone (TSH) levels (Sawicka et al, 2010) and rise to normal levels with pharmacological therapy of hyperthyroidism (Braclik et al, 2008;GimenezPalop et al, 2005;Riis et al, 2003;Rojdmark et al, 2005;Theodoropoulou et al, 2009).…”
Section: Page 21 Of 44mentioning
confidence: 99%
“…Insulin resistance is increased in hyperthyroidism (Gimenez-Palop et al, 2005) and hyperinsulinaemia has been shown to suppress ghrelin levels (Saad et al, 2002) regardless of thyroid status (Riis et al, 2003).…”
Section: Page 21 Of 44mentioning
confidence: 99%